Interactions of genetic variants and prenatal stress in relation to the risk for recurrent respiratory infections in children - Laura S. Korhonen (Nature Portfolio, 2021)
Abstract Genetic variants may predispose children to recurrent respiratory infections (RRIs) but studies on genotype-environment interaction are rare. We hypothesized that the risk for RRIs is elevated in children with innate immune gene variants, and that prenatal exposure to maternal psychological distress further increases the risk. In a birth cohort, children with RRIs (n = 96) were identified by the age of 24 months and compared with the remaining cohort children (n = 894). The risk for RRIs in children with preselected genetic variants and the interaction between maternal distress during pregnancy and child genotype were assessed with logistic regression. The IL6 minor allele G was associated with elevated risk for RRIs (OR 1.55; 95% CI 1.14–2.12). Overall, there was no interaction between maternal psychological distress and child genotype. Exploratory analyses showed that, the association between the variant type of IL6 and the risk for RRIs was dependent on prenatal exposure to maternal psychological distress in males (OR 1.96; 95% CI 1.04–3.67). Our study didn’t find genotype-environment interaction between prenatal maternal distress and child genotype. Exploratory analyses suggest sex differences in gene-environment interaction related to susceptibility to RRIs.